High‐Yield Synthesis of Silver Nanoclusters Protected by DNA Monomers and DFT Prediction of their Photoluminescence Properties1. Issue 7 (9th January 2013) - Yang, Xuan; Gan, Linfeng; Han, Lei; Wang, Erkang; Wang, Jin
<x xml:space="preserve">Abstract</x> Basic evidence is provided for the benefits of using cytosine‐rich DNA strands as scaffolds for fluorescent silver nanoclusters. The DFT‐calculated fluorescence spectra of silver nanoclusters (AgNCs) protected by DNA monomers (dC, dA, dT, and dG) were in good agreement with the experimentally obtained spectra (see picture), showing that only the use of cytosine‐rich DNA strands as scaffolds gives fluorescent nanoclusters.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>